Penambahan angkak (monascus purpureus) pada tempe dalam peningkatan antioksidan - Lusiawati Dewi; Marisa Christina Tapilouw; Ega Meilenia Putri Pamungkas (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2022)
Tempe is a fermented food product that can be consumed as an energy source. The use of soybeans as a basic ingredient and the addition of Angkak can improve the quality of tempeh such as increasing its water content and antioxidants. The purpose of this study was to determine the effect of giving Angkak at a certain concentration on the quality of tempeh. The study used a single pattern Completely Randomized Design (CRD) where 1 factor was the administration of Angkak at a certain concentration with each treatment 5 times. The result of this research is that there is an effect of giving Angkak at a certain concentration on the quality of tempeh. The highest antioxidant activity was found in tempeh with an additional concentration of 1.5% (4532.01ppm). The addition of Angkak also affects the moisture content of tempeh, which increases due to the hygroscopic condition of the Angkak powder. In addition, from the organoleptic test, it was found that the addition of Angkak at a concentration of 1% was more in demand by respondents than concentrations of 0%, 0.5%, and 1.5%.